2012
DOI: 10.1111/aogs.12020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antenatal recognition and follow‐up on perinatal outcomes in small‐for‐gestational age infants delivered after 36 weeks

Abstract: Antenatal recognition of late SGA may improve perinatal outcomes. However, admission to neonatal intensive care and cesarean delivery were more frequent among SGA infants recognized antenatally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
42
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 24 publications
10
42
3
Order By: Relevance
“…These results from the French context are concordant with previous studies which also documented low detection rates for SGA . One reason may be that the effectiveness of ultrasound and symphysis–fundal height measurement for the detection of FGR is poor .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results from the French context are concordant with previous studies which also documented low detection rates for SGA . One reason may be that the effectiveness of ultrasound and symphysis–fundal height measurement for the detection of FGR is poor .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies of antenatal detection of FGR came from selected hospitals or covered a limited geographical zone . Further, these studies only included SGA infants . Our study made it possible to quantify the proportions of non‐SGA infants suspected of FGR during pregnancy and to investigate their obstetric management and neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was detected as frequently as 69.5% in our study, it might have been arisen because the diagnoses of SGA were made antenatally. Likewise, Fratelli et al showed that cesarean delivery rates of women who were diagnosed antenatally as they had SGA babies were significantly higher than women who were diagnosed in postpartum period (8).…”
Section: Discussionmentioning
confidence: 99%
“…Late‐onset FGR is also associated with increased perinatal morbidity in the form of fetal distress, hypoglycemia, seizures, behavioral problems, cerebral palsy and cardiovascular disease. There are, however, other potential risks, including increased NNU admission, childhood morbidity and ‘medicalization’. What are not clear are the respective roles of GA at delivery, birth weight or pregnancy characteristics associated with early‐term delivery.…”
Section: Discussionmentioning
confidence: 99%